Symbolic ethnicity, cultural and linguistic landscape: remnants of 'Little Europe' in the Valcanale (Northeast Italy) - Plautz, Anna-Maria; Hasenauer, Leonie; Jelen, Igor; Čede, Peter; Steinicke, Ernst (National identities, 2022)
This study investigates 'Little Europe', the rural, mountainous Italian region of the quadrilingual Valcanale, bordering Austria and Slovenia. The combined analysis of cultural landscape, linguistic landscape (LL) and symbolic ethnicity provides a new concept to examine multilingual regions. In this once Austrian valley, where German was the official language before WWI, Italian now dominates over minority languages, as exemplified by official signs. However, elements of the area's cultural and linguistic landscape reveal unexpected linguistic practices and visible, locatable artefacts of the Valcanale's ethnolinguistic heritage, which we assume to play a key role in the preservation of symbolic ethnicity.